Experimental Investigation and Lumped-parameter Model of the Cooling System of an ICE under Nucleate Boiling Conditions. (December 2015) - Bova, S.; Castiglione, T.; Piccione, R.; Pizzonia, F.; Belli, M.
Abstract: The work presents the results of experimental tests, which were carried out on a small-displacement spark ignition engine, where a low flow rate electric pump was used to substitute the standard crankshaft-driven one. The engine was then operated both under usual single-phase heat transfer regime and under nucleate boiling conditions. The engine was properly instrumented in order to record coolant pressure, temperature and flow rate as well as metal temperatures. The experimental investigation was coupled with the development of a dynamic lump-parameter model of the engine cooling system. The model calculates the spatial averaged metal temperature, the engine-out coolant temperature and the fraction of metal heat transfer area which is involved in nucleate boiling as a function of engine-in coolant flow rate, pressure and temperature, fuel mass flow rate and engine speed. The experimental data and the model results show a good agreement and the model is suitable to develop a coolant flow rate control system. This facilitates faster engine warm-up, lower fuel consumption and lower CO2 emissions, which can be significant under low-load and cold-start conditions.